2020
DOI: 10.1002/ps.5921
|View full text |Cite
|
Sign up to set email alerts
|

A point mutation in the β‐adrenergic‐like octopamine receptor: possible association with amitraz resistance

Abstract: Background: Amitraz is a unique formamidine-class acaricide/insecticide that effectively controls ticks, mites, and insect pests. However, the recent emergence of amitraz-resistant cattle ticks is a serious problem that requires an urgent solution. A nonsynonymous single nucleotide polymorphism (A181T) leading to an amino acid substitution (I61F) in the ⊎-adrenergic-like (⊎-AL) octopamine receptor (OAR) of amitraz-resistant southern cattle ticks (Rhipicephalus microplus) (Rm⊎AOR) was proposed to be a cause of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
(54 reference statements)
0
21
0
Order By: Relevance
“…Moreover, DPMF was confirmed to be a more potent octopamine receptor agonist than amitraz itself, indicating that amitraz undergoes metabolic activation. Site-directed mutagenesis studies clearly showed that amitraz and DPMF act as orthosteric antagonists [73]. These groundbreaking studies provided evidence that targetsite insensitivity significantly contributes to the widespread amitraz resistance [73].…”
Section: Octopamine Receptors As Molecular Targets Of Insecticidesmentioning
confidence: 98%
“…Moreover, DPMF was confirmed to be a more potent octopamine receptor agonist than amitraz itself, indicating that amitraz undergoes metabolic activation. Site-directed mutagenesis studies clearly showed that amitraz and DPMF act as orthosteric antagonists [73]. These groundbreaking studies provided evidence that targetsite insensitivity significantly contributes to the widespread amitraz resistance [73].…”
Section: Octopamine Receptors As Molecular Targets Of Insecticidesmentioning
confidence: 98%
“…For instance, OARs have drawn widespread attention as targets for formamidine-type insecticides/ acaricides [chlordimeform, amitraz and N-2,4-dimethylphenyl-N 0methylformamidine (DPMF), a metabolite of amitraz], and are crucial in the development of current insecticides. [13][14][15] OARs can be further grouped as either ⊍-OARs (⊍-adrenergic-like octopamine receptors) or ⊎-OARs (⊎-adrenergic-like octopamine receptors) according to their sequence homology. 16 ⊎-OARs are further put into three categories according to differences in their genetic and functional characterization.…”
Section: Introductionmentioning
confidence: 99%
“…A correlation analysis of the mutation frequency and the phenotypic traits confirmed the I61F site mutation to be associated to amitraz resistance 15 . This conclusion was further verified in the silkworm cell line 17 . Besides the octopamine receptors, ATP‐binding cassette transporters (ABC transporters) have also been shown to be involved in the detoxification and transport of amitraz metabolites.…”
Section: Discussionmentioning
confidence: 72%
“…15 This conclusion was further verified in the silkworm cell line. 17 Besides the octopamine receptors, ATP-binding cassette transporters (ABC transporters) have also been shown to be involved in the detoxification and transport of amitraz metabolites. Through immunolocalization and RNAi analysis, it was previously found that ABCB10 of R. microplus can transport and detoxify amitraz in midgut cells 89 ; subsequent analysis of differential gene expression confirmed the high expression level of this transporter in acaricideresistant cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation